Efficacy and Safety of Probiotics in Irritable Bowel Syndrome: A Systematic Review and Meta-Analysis - Li, Bing; Liang, Li; Deng, Huijie; Guo, Jinmin; Shu, He; Zhang, Li (Frontiers in Pharmacology, 2020)
Background Irritable bowel syndrome is a common functional gastroenterological diseases. Evidence suggests that probiotics may benefit IBS symptoms. However, trials have been conflicting. Aims To perform a systematic review and meta-analysis to examine the efficacy and safety of probiotics in IBS. Methods We searched Medline, PubMed, Embase, the Cochrane Central Register of Controlled Trials, the ClinicalTrials.gov trials register and Chinese Biomedical Literature Database for relevant trials before Jan 1, 2019. Dichotomous data were pooled to obtain the relative risk (RR) with a 95% confidence interval (CI). Continuous data were pooled using a standardized mean difference (SMD) with a 95% CI. Results We included data from 60 trials including 6761 patients. The RR of improvement or response with probiotics vs. placebo was 1.52 (95% CI 1.32-1.76), with statistically significant heterogeneity detected between studies (I 2 = 71%, P < 0.001). It was not possible to draw definitive conclusions about the efficacy. Differences were detected in the subgroup analyses of probiotic type, dose, and treatment duration . Adverse events were no more common with probiotics. Conclusion Probiotics are effective and safe therapy for IBS patients. Single probiotics, a high dose and a short treatment duration appear to be more effective in improving IBS symptom, but more evidence for these effects is still needed.